Role of Sport Psychology in Sports and Physical Education: Exploring the Psychological Factors in Sports Performance (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The capacity of the person to manage mental emotional elements assists task success as well as providing a psychological basis for trust health. Psychology of the sportsperson is very important for achieving the heights in sports. It includes various components physical, mental, spiritual and good emotional health of the sportsperson. Psychology includes the various components like personality attitudes, anxiety, aggression and stress also play a vital role in sports. This paper identifies all these factors and their importance for the sportsperson to become the elite and successful sportspersons in their life.